Constitution 3.0 : freedom and technological change - Rosen, Jeffrey, 1964-; Wittes, Benjamin (Washington, D.C. : Brookings Institution Press, 2011)
'Explores the challenges to constitutional values posed by sweeping technological changes such as social networks, brain scans, and genetic selection and suggests ways of preserving rights, including privacy, free speech, and dignity in the age of Facebook and Google'--
Introduction: technological change and the constitutional future / Jeffrey Rosen -- Is the Fourth Amendment relevant in a technological age? / Christopher Slobogin -- Use restrictions and the future of surveillance law / Orin S. Kerr -- Cyberthreat, government network operations, and the Fourth Amendment / Jack Goldsmith -- The deciders : Facebook, Google, and the future of privacy and free speech / Jeffrey Rosen -- Is filtering censorship? : the second free speech tradition / Tim Wu -- A mutual aid treaty for the Internet / Jonathan Zittrain -- Neuroscience and the future of personhood and responsibility / Stephen J. Morse -- Cognitive neuroscience and the future of punishment / O. Carter Snead -- Reproductive rights and reproductive technology in 2030 / John A. Robertson -- The problems and possibilities of modern genetics : a paradigm for social, ethical, and political analysis / Eric Cohen and Robert P. George -- Endowed by their creator? : the future of constitutional personhood / James Boyle -- Innovation's darker future: biosecurity, technologies of mass empowerment, and the Constitution / Benjamin Wittes -- Epilogue: translating and transforming the future / Lawrence Lessig.
Includes bibliographical references and index.
Keywords: Constitutional law -- United States; Technology and law -- United States; Civil rights -- United States; Information technology -- Law and legislation -- United States; Freedom of expression -- United States; Privacy, Right of -- United States